2002
DOI: 10.1053/joca.2002.0517
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the pericellular microenvironment on the chondrocyte response to osmotic challenge

Abstract: The composition and structural integrity of the pericellular microenvironment do influence the cellular response to experimental osmotic challenge. This suggests that the microenvironment functions in situ to mediate the chondrocyte response to physicochemical changes associated with joint loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 50 publications
6
55
0
1
Order By: Relevance
“…Similarly endothelial cells forming the lining of blood vessels experience deformation through a combination of fluid shear and circumferential mechanical stretch of the tissue [15]. In addition, changes in extracellular osmotic pressures may trigger cell deformation in the form of volumetric changes [13,21,34]. Clearly, a range of different loading parameters and in vitro cell based model systems are therefore required to investigate physiological deformation in different cell types.…”
Section: Mechanical Loading Systems For the Study Of Cell Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly endothelial cells forming the lining of blood vessels experience deformation through a combination of fluid shear and circumferential mechanical stretch of the tissue [15]. In addition, changes in extracellular osmotic pressures may trigger cell deformation in the form of volumetric changes [13,21,34]. Clearly, a range of different loading parameters and in vitro cell based model systems are therefore required to investigate physiological deformation in different cell types.…”
Section: Mechanical Loading Systems For the Study Of Cell Deformationmentioning
confidence: 99%
“…Of course 3D imaging is not essential if the cell can be considered symmetrical in the z plane. Hence for spherical cells, such as isolated chondrocytes subjected to hyper-or hypoosmotic cell deformation, the cell volume can be estimated from measurements of cell diameter (D) or area (A) made from brightfield or 2D confocal images bisecting the centre of the cell [34] (Eq. (4)).…”
Section: Confocal Microscopy For Quantification Of 3d Cell Deformationmentioning
confidence: 99%
“…In particular, it is known that the PCM surrounding the chondrocyte organizes and constructs collagen fibrils ] regulates cellular osmolarity [Hing et al 2002] and modulates growth factor interactions with the enclosed cell [Ruoslahti and Yamaguchi 1991]. The mechanical properties of the PCM are known to differ from the larger territorial and interterritorial matrices inside the cartilage tissue and are approximately 10-fold greater in stiffness than the enclosed chondrocyte [Guilak et al 1999;Guilak and Mow 2000;Alexopoulos et al 2003;Alexopoulos et al 2005b;Alexopoulos et al 2005a].…”
Section: Cellular Microenvironmentmentioning
confidence: 99%
“…Chondrons, which are composed of a chondrocyte and its surrounding PCM or microenvironment, are the basic anatomical, functional, and metabolic unit of cartilage (Poole et al 1987;Poole 1997). The physical properties of chondrons, such as mechanical strength and resistance to osmolarity changes, are superior to chondrocytes alone (Guilak et al 1999;Hing et al 2002;Knight et al 2001). Through chondron studies, the PCM has been shown to profoundly influence chondrocytes on matrix production (Graff et al 2003;Larson et al 2001) and global gene expression (Zhang et al 2006).…”
Section: Introductionmentioning
confidence: 99%